A Meta Protocol for Adaptable Mobile Replicated Databases - Fritzke Jr., Udo; Gomes, Luiz Alberto F.; Silva, Denis L.; Morais, Daniel M. (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2007: Anais do VIII Workshop de Testes e Tolerância a Falhas, 2007)
This paper presents a meta protocol that allows the replacement of replication control protocols in mobile replicated databases. The meta protocol is motivated by the adaptability requirements of mobile database systems but can also be used on replicated databases with fixed nodes. The paper defines three properties that meta protocol executions have to enforce and specifies a protocol that satisfies these properties. The protocol is based on transactions and atomic broadcast. Finally, we outline a dynamic adaptable architecture that includes the meta protocol and that is based of an aspect oriented framework and on a group communication system.